Developing a Model of Students’ Understanding of Islamic Banking Accounting Based on Learning Experiences: A Grounded Theory Approach - Saputra, Wali (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
Islamic banking accounting carries unique complexities as it integrates technical accounting procedures with Sharia principles. Students’ understanding of Islamic accounting is critical for preparing competent graduates capable of contributing to the growth of the Islamic finance industry. However, how students construct their understanding of Islamic banking accounting through their learning experiences has not yet been comprehensively mapped. This study aims to develop a theoretical model of students’ understanding of Islamic banking accounting based on their learning experiences using a Grounded Theory approach. This qualitative research employed the Grounded Theory method and involved 24 students from three Indonesian universities who had completed coursework in Islamic banking accounting. Data were collected through in-depth interviews, focus group discussions, and documentation analysis. Data analysis followed the three-stage coding procedure (open, axial, and selective coding) with the assistance of NVivo 12 software. The study produced a Progressive Spiral Model of Islamic Accounting Understanding, showing that students’ comprehension develops iteratively through three interrelated layers: (1) the technical–procedural layer focusing on mastering transaction recording mechanisms, (2) the conceptual–Sharia principles layer connecting accounting practices with Islamic ethical values, and (3) the philosophical–maqashid layer integrating accounting with the broader objectives of Sharia in socioeconomic contexts. This progression is facilitated by four key conditions: prior knowledge architecture, pedagogical approaches, community of practice, and personal motivation. Students employ cognitive, metacognitive, and social strategies to deepen their understanding. The study identifies four typologies of student understanding: Technical Performers, Conceptual Understanders, Integrated Learners, and Reflective Scholars. The Progressive Spiral Model contributes theoretically to accounting and Islamic economics education literature by demonstrating that the development of understanding is spiral and iterative rather than linear. Practical implications include the need for curriculum designs that support progression across the three layers of understanding, integration of experiential learning and reflective practice, creation of communities of practice, and development of comprehensive assessment frameworks. The model provides a foundation for designing more effective learning strategies in Islamic banking accounting education.